Optimality conditions and duality results for generalized-Hukuhara subdifferentiable preinvex interval-valued vector optimization problems - Peng Z.-Y.; Peng J.-Y.; Ghosh D.; Zhao Y.; Li D. (My University, 2025)
This study investigates a class of preinvex vector interval optimization problems (VIOP) involving gH-subdifferentiable functions and derives both optimality conditions and duality results. At first, a definition of subgradient for preinvex interval-valued function under gH-difference is given; examples are provided to verify the difference between the subgradient in this paper and the existing ones. Next, by means of gH-subdifferential, the Karush-Kuhn-Tucker sufficient and necessary optimality conditions for preinvex VIOP are studied. Then, the Mond-Weir and Wolfe duality results for VIOP with preinvex functions are established. Weak duality, strong duality, and converse duality theorems are reported by using the proposed gH-subdifferential. Some examples are given to illustrate the main results. To some extent, the main results generalize the existing relevant results. © 2025 Elsevier B.V.